The impact of organisational reform measures on managerial global mindset intensity: empirical evidence from Indian and Chinese service industry managers - Ananthram, Subramaniam; Chatterjee, Samir (Ryukoku University, 2007)
The cognitive orientations of managers in processing fast moving global knowledge structures have become critical as corporations around the world make sense of the upheavals of globalisation. As Chinese and Indian firms make unprecedented marks in the global arena, significant reforms and mindset reorientations are emerging as areas of scholarly attention. The capability of intensification of global mindset in terms of synthesising multiple organisational imperatives, structural and technological diversities and entrepreneurial cultures are being impacted by national, organisational and managerial level reforms in these two countries. The study presented in this paper compares some of the identified determinants of global mindsets of managers in the service sector in India and China. Based on a study of 239 Indian and 210 Chinese managers, the results suggest that there is an increasing level of leveraging organisational level reforms evident in both countries as they seek to extend their global visibility and advantage.